Modeling the open market operations of the Bangko Sentral ng Pilipinas for use in the conduct of monetary policy analysis - Torreja, Magno Luna, Jr. (Animo Repository, 1999)
In line with the mandate of the Bangko Sentral ng Pilipinas (BSP), the Bank specifically adopted a low and stable inflation rate (IR) as the ultimate target of monetary policy and used domestic liquidity or M3 and Reserve Money (RM) as the intermediate and operating targets, respectively. Monetary targeting in the Philippines is undertaken through the use of the following monetary policy instruments: Open market operations (OMO) Reserve Requirement (rr) Rediscounting Government Deposits and Moral Suasion. The instruments used in the conduct of OMO are the following: Repurchase Agreements (RP) Reverse Repurchase Agreements (RRP), and Outright Contracts.Since 1970, a number of local studies were conducted to determine the effectiveness of the monetary policy instruments used by the old Central Bank of the Philippines (CBP). Some of these studies, including those of Sangoyo (1970), Ocampo (1976), Tan (1972), and Lacerna (1981), concluded that the monetary policy instruments used by CBP are not effective. A recent study by Rufino (1997) drew also the following conclusions: (a) the emergence of increasing volatility of the different money multipliers over the years, (b) structural instability of the basic equation linking the changes in the aggregates and the changes in RM, and (c) structural shift in the financial system. Moreover, it is to be noted that the country undertook a number of policy and institutional reforms in its financial sector during the past one and a half decades. This study aims to (a) develop a new OMO model using the Vector Auto Regression (VAR) approach for the BSP in light of the recent changes and reforms in the financial system, and (b) determine the degree of relationship between the present OMO model and the monetary policy targets. This study found out that (a) under the new OMO model, the sales/redemption of government securities (GS), and maturity structures of loans have feedback relations with RM (b) the VAR is not able to pick up significant feedback relationship among the IR, M3 and RM (c) the cointegration test results, likewise, indicate that the IR, ME, and RM are not cointegrated, that is to say, a long-term relationship among the three variables does not exist and (d) of the present OMO instruments, only the overnight RRP and sales/redemption of GS have feedback relations with RM while none was detected with IR and M3.Thus, the study recommends that the monetary authority should look closely at the variables found to have feedback relations with RM and likewise should consider the absence of feedback relations among the monetary targets in the conduct of monetary policy analysis.